Information Technology Strategic Planning for Portfolio Application in Hospitality Industry - Gunawan, Irwan Prasetya; Yesmaya, Violitta; Saragih, Hoga (Journal of Computer and Information, 2012)
Information technology is now used to allow users to manage information more quickly and effectively. Advances in technology in the hospitality  industry have evolved over the years. Strategic planning is implemented by companies/organizations to increase competitive advantage, minimize competitive disadvantage, and improve business process. This paper aims at producing IT strategic planning in the  hospitality industry to support the business process in a hotel. The method used in this research was adopted from a framework of IT Strategic Planning by Ward (2002). This study also used several measures such as SWOT and Porter's 5 Forces to analyze the  internal and external business environment of the hotel subject in this study. The results were a portfolio of new applications such as Mobile Web Application, CRM and Knowledge Management System which are proposed for the IT strategic planning in the hospitality industry.